Hubungan Pengetahuan dan Perilaku Lansia Terhadap Pencegahan Asam Urat di Puskesmas Tampahan Kecamatan Tampahan Kabupaten Toba Tahun 2023 - Erita Saragih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Uric acid is a metabolic waste in the form of purine crystals that are naturally present in the blood. Normal uric acid levels in the blood of adult men are 3.5 – 7.2 mm/dl and in women 2.6 – 6.0 mg/dl. Purine substances are natural substances which are one of a group of chemical structures that make up DNA and RNA derived from the body's own production and from food. This study aims to determine the relationship of knowledge and behavior of the elderly to the prevention of increased gout at the Tampahan Health Center, Tampahan District, Toba Regency. This research was conducted from Oktober to Desember 2023. Behavioral relationships. This research is a quantitative study using a Cross-sectional Design. The population in this study were all gout sufferers who came for treatment at the Tampahan Health Center, Tampahan District, Toba Regency. The sample size was 35 respondents using a questionnaire. Data analysis used Chi-square test with significance level = 0.05. From the results of research on 35 respondents showed that the majority were knowledgeable enough as many as 20 people (57.1%), the majority of behavior was in the good category as many as 17 people (48.6%). While the majority for prevention in the good category were 27 people (80.0%). There is no relationship between the knowledge of the elderly about gout and the prevention of increased gout where X2 count < X2 table and there is a relationship between the behavior of the elderly with gout on the prevention of increased gout where the chi-square test X2 count > X2 table. For the elderly with gout to further increase their knowledge about preventing an increase in uric acid and pay attention to their health, especially in reducing consumption of high-protein foods and diligently self-examination to the health center.